2017
DOI: 10.1155/2017/8254289
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Mechanism of Polyphenols and Nrf2 Signaling Pathway in LPS Challenged Pregnancy Disorders

Abstract: Early embryonic loss and adverse birth outcomes are the major reproductive disorders that affect both human and animals. The LPS induces inflammation by interacting with robust cellular mechanism which was considered as a plethora of numerous reproductive disorders such as fetal resorption, preterm birth, teratogenicity, intrauterine growth restriction, abortion, neural tube defects, fetal demise, and skeletal development retardation. LPS-triggered overproduction of free radicals leads to oxidative stress whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 134 publications
(133 reference statements)
1
19
0
Order By: Relevance
“…Subsequently, the relationship between mi-34a and LGR4 was identi ed by the dual-luciferase reporter assay, which showed that miR-34a drastically lowered the activity of LGR4 3'UTR. Similarly, it has been recently reported that LGR4 is a common target of miR-34a and miR-34c in mice [30]. In conjunction with the above study results, that LGR4 inhibits the production of pro-in ammatory mediators, subsequently, we transfected miR-34a mimic or inhibitor to BENDs to carry out function gain and function loss experiments in order to further investigate whether there was a suppression effect of miR-34a on LGR4.…”
Section: Discussionsupporting
confidence: 70%
“…Subsequently, the relationship between mi-34a and LGR4 was identi ed by the dual-luciferase reporter assay, which showed that miR-34a drastically lowered the activity of LGR4 3'UTR. Similarly, it has been recently reported that LGR4 is a common target of miR-34a and miR-34c in mice [30]. In conjunction with the above study results, that LGR4 inhibits the production of pro-in ammatory mediators, subsequently, we transfected miR-34a mimic or inhibitor to BENDs to carry out function gain and function loss experiments in order to further investigate whether there was a suppression effect of miR-34a on LGR4.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, probiotics have positive impacts on colonized beneficial bacterial and growth performance in broilers and pigs (Jeong and Kim, 2014; Valeriano et al, 2017). Noticeably, probiotics, as the alternatives for antibiotics used to prevent poultry diseases and improve production performance, have been demonstrated to be beneficial to chickens’ growth performance and health, such as the increases of body weight (BW), feed conversion efficiency, immune response, resistance to bacterial infection, and regulation of intestinal microflora (Xu et al, 2012; Cao et al, 2013; Song et al, 2014; Clavijo and Flórez, 2017; Haque et al, 2017; Hussain et al, 2017a; Azad et al, 2018; Mashayekhi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum absorption peaks of p -hydroxybenzoic acid or hydroxycinnamic acid are detected at 280 and 320 nm, respectively [ 17 , 18 ]. Ferulic acid inhibits the production of tumour necrosis factor- (TNF-) α in RAW264.7 cells stimulated with lipopolysaccharide (LPS) [ 19 , 20 ]. Immunological studies have shown that phenyl ethyl caffeate strongly and significantly inhibits the expression of interferon gamma-induced protein- (IP-) 10 in response to TNF, as well as the production of lymphoid factors and activation of nuclear factor- (NF-) κ B [ 21 23 ].…”
Section: The Structure and Function Of Polyphenolsmentioning
confidence: 99%